Math, asked by sfaditya155, 1 year ago

5pq(p2-q2)÷2p(p+q)
solve this please fast

Answers

Answered by jish4you
101
hi aditya,

5pq(p^2 - q^2) / 2p(p+q)
= 5pq(p+q)(p-q) / 2p(p+q)
= 5q(p-q) / 2
= 5/2(pq - q^2)

Hope it helped.

Answered by kushanaanandp4ac8a
44
5pq(p2-q2)÷2p(p+q).
As we know that a2-b2 = (a-b)(a+b).
Applying same to p2-q2 = (p+q)(p-q).
Now expanding and dividing.
5pq(p2-q2)÷ 2p(p+q).
5pq(p+q)(p-q)/2p(p+q).
p(p+q) will be cancelled out from numerator and denominator, leaving values
5q(p-q)/2.
Or we can also write it as,
5/2pq-5/2q2.

Hope it helps.
Similar questions